OP92 The Impact of Military Deployment, Combat Experiences and Post-Deployment Mental Health Problems on Violent Behaviour among UK Military Personnel. (17th September 2012) - MacManus, D; Dean, K; Jones, M; Rona, R; Hull, L; Greenberg, N; Fahy, T; Wessely, S; Fear, N
Abstract : Background: There is considerable media, political and public interest on both sides of the Atlantic in an alleged rise in violence among military personnel returned from conflicts in Iraq and Afghanistan. This study explores violence among a large sample of UK military personnel, a proportion of whom had been deployed to Iraq/Afghanistan. The aims were to estimate the prevalence of self-reported violence, examine the impact of deployment and combat experiences on subsequent violence and the association with post-deployment mental health problems and alcohol misuse. Methods: This study formed part of a questionnaire-based cohort study established to explore the impact of deployment on mental health among UK military personnel. The sample was randomly selected from all military personnel serving in the UK Armed Forces between 2003 and 2007. A total of 9986 participants from all Services were included, some had been deployed and some had been trained but not deployed. Special Forces were excluded. Data, collected by questionnaire, included information on deployment experiences, socio-demographic and military characteristics, pre-enlistment antisocial behaviour, and post-deployment health outcomes. The main violence outcomes were self –report measures of interpersonal violence. Results: 6.2% of the sample reported interpersonal violence in the last month. Deployment showed a stronger association with subsequent violence among reservists (OR=2.98 (1.50–5.93), P=0.002) than among regulars (OR=1.26 (0.96–1.67), P=0.098) when compared to their non-deployed counterparts. Performing a combat role whilst deployed was associated with a significantly increased likelihood of violence among regulars (OR=1.90 (1.38–2.75), P<0.001) and the risk of violence increased with the number of traumatic events experienced (P<0.001)). Violence on homecoming was also associated with mental health problems such as PTSD (OR=4.8 (3.2–7.2) P<0.001) and alcohol misuse (OR=3.1 (2.5–3.9) P<0.001). Conclusion: Military deployment, in particular combat exposure, increased the risk of subsequent violence among military personnel and the risk of violence increased with increasing number of traumatic events experienced on deployment. Valuable information on risk factors for violence among military personnel is provided, especially regarding increased risk among deployed reservists and among personnel who report post-deployment mental health problems and alcohol misuse.